Advancements and Emerging Trends in Thermal Energy Storage Technologies for Sustainable Energy Systems - Shrihar Pandey (International Journal of Electrical Machine Analysis and Design, 2025)
Rising global energy demand and environmental concerns have led researchers to investigate renewable energy sources as alternatives to fossil fuels. Solar and wind power have emerged as key players in the transition to more sustainable energy systems. Thermal energy storage (TES) technologies are critical to addressing the variability of renewable energies, allowing for a better management of energy, improved reliability, etc. This paper analyses the recent advances in the field of thermal energy storage; it categorizes them into sensible heat storage (SHS), latent heat storage (LHS), and thermochemical energy storage. A description of each type is examined, outlining its principle, material, behaviour, applications, and therefore constraints, with high regard to recent developments. TES is placed within the context of renewable energy systems, such as Concentrated Solar Power (CSP) and wind energy, to highlight its efficiency and system stability improvement potential. In addition, its application in manufacturing, residences, transport, and healthcare shows its multifaceted nature while aiding in cutting down energy costs and emissions. This review emphasizes the cruciality of TES in achieving sustainability-related goals and identifies the emerging trends and challenges for future development.
Keywords: Phase change materials; Thermal Energy Storage; energy efficiency; grid stability; renewable energy integration; sustainable energy systems